Semantic technologies for distributed information systems - Haase, Peter (KIT Scientific Publishing, 2007)
In this book we show how semantic technologies and in particular the use of ontologies can be employed to address a number of typical challenges in distributed information systems: First, we illustrate how ontologies enable the integration of information across heterogeneous nodes. Second, we show how ontology evolution allows dealing with the dynamics in the information in a consistent manner. Third, we present a model for ontologybased coordination using semantic overlay networks.